Peningkatan Literasi Keuangan terhadap Siswa/i SMA IT Pesantren Nururrahman Depok - Murti Dewi Widowati Hermajiwandini, Chandra; Suhartono, Suhartono; Febrianti, Rini; Pradana, Hasta Dwi; Ulfah, Indar Fauziah (Universitas Terbuka, 2024)
The rapid development of financial literacy is due to the presence of digital technology, which enables people from all walks of life to access various financial services. Although the financial regulator, OJK, has imposed strict age restrictions and requirements for accessing these financial facilities, many members of the general public, especially students, neglect the requirements when accessing financial services, leading to a phenomenon where many students or university students become entangled in online loans and even e-commerce transactions that facilitate borrowing. Therefore, this service aims to provide education or socialization to the public, especially students, to better understand financial literacy and thoroughly discuss the impacts and benefits. The students selected for this service are from SMAIT Nururrahman, located at Jl. Raya Sawangan No.11, Pancoran MAS, Pancoran Mas District, Depok City, West Java 16436.